Local and regional weather patterns influencing post‐breeding migration counts of soaring birds at the Strait of Gibraltar, Spain. (23rd November 2015) - Miller, Robert A.; Onrubia, Alejandro; Martín, Beatriz; Kaltenecker, Gregory S.; Carlisle, Jay D.; Bechard, Marc J.; Ferrer, Miguel
Abstract : Migration is a significant event in the annual cycle of many avian species. During migration birds face many challenges, including unfamiliar foraging and refuge habitats, resulting in a much higher rate of mortality during migration than during other seasons of the year. Weather may significantly affect a bird's decision to initiate migration, the course and pace of migration, and its survival during migration. Each of these influences may impact the counts of migrating birds at geographical convergence zones or bottlenecks. It is important to quantify the effect of short‐term weather on these counts to appropriately interpret and use such counts in other analyses. To this end, we aim to assess the effects of local and regional weather conditions on the migration counts of soaring birds at the Strait of Gibraltar during post‐breeding migration. We used information‐theoretic approaches to analyse the influence of local weather and weather in northern Spain on the migration counts of five soaring bird species from two count sites near the Strait of Gibraltar. Migration counts were higher on days with local northerly and westerly winds, often following a day of easterly winds, on days with local high pressure systems, and often following a day of lower pressure. Weather conditions in northern Spain influenced migration counts at the Strait of Gibraltar, but the effects were much weaker than local weather conditions. We confirm that short‐term weather conditions, locally and regionally, can influence migration counts and should thus be considered when these counts are used in other analyses.